Peranan Arbitrase dalam Penyelesaian Perselisihan Hubungan Industrial Implikasi, Keuntungan dan Kelemahan - Gultom, Walman; Ansari, Teuku Syahrul; Koswara, Indra; Pura, Margo Hadi (Peneliti.net, 2023)
There are times when disputes with regret in industrial relations are regulated by Law Number 2 of 2004, namely the regulation of the procedure for resolving problems arising from industrial relations conflicts, the dispute resolution process can be passed from the mechanism outside the court or special court that specifically handles disputes in that field. The content of this research utilizes the normative juridical method as the research approach. This method involves tracing various secondary materials, such as laws and regulations. This research aims to analyze the legal framework governing the recognition and enforcement of foreign arbitral awards in Indonesia and Singapore, as well as to compare the differences and similarities between the legal frameworks in Indonesia and Singapore in terms of recognition and enforcement of foreign arbitral awards. Arbitration plays an important role in the out-of-court settlement of industrial relations disputes. In this study, several advantages of arbitration have been identified, such as cost and time efficiency, high level of confidentiality, legal certainty, and flexibility in settlement procedures.